2020
DOI: 10.1111/1471-0307.12708
|View full text |Cite
|
Sign up to set email alerts
|

Milk products fermented byLactobacillusstrains modulate the gut–bone axis in an ovariectomised murine model

Abstract: Limited information is available regarding the effect of Lactobacillus on the gut-bone axis. We examined whether 10-week administration of milk products fermented by Lactobacillus fermentum MF27 and/or Lactobacillus casei 393 modified gut-bone dysbiosis induced by ovariectomy and lipopolysaccharide (OVX-LPS) in rats. The fermented milk products selectively modulated gut microbiota composition and improved intestinal barrier function; they suppressed osteoclastogenesis, thereby increasing trabecular bone volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 70 publications
(68 reference statements)
0
17
0
1
Order By: Relevance
“…According to Eor et al (2020), the milk product fermented by single LAB strain decreased osteoporosis in the rat model by decreasing gut inflammation. Additionally, the authors who performed human trial insisted that different kinds of dairy product consumption might be resulted in different results, suggesting that probiotic Prato cheese showed the best postprandial glycaemia reduction activity (Grom et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to Eor et al (2020), the milk product fermented by single LAB strain decreased osteoporosis in the rat model by decreasing gut inflammation. Additionally, the authors who performed human trial insisted that different kinds of dairy product consumption might be resulted in different results, suggesting that probiotic Prato cheese showed the best postprandial glycaemia reduction activity (Grom et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, myeloperoxidase (MPO) levels were significantly low after RA induction, but each treatment restored MPO activity against RA induction ( Fig. 2D ); restoration of MPO activity was previously indicated as the anti-oxidative and anti-inflammatory activity ( Eor et al, 2020 ).…”
Section: Resultsmentioning
confidence: 68%
“…The β-actin as the housekeeping gene. The expression of mRNA levels each genes of analyzed samples were analyzed with calculation using Bio-Rad CFX manager software (Bio-Rad) ( Eor et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent year, there is added probiotic in several commercial food such as non-dairy foods matrices (Rasika et al, 2021) and dairy (Hadjimbei et al, 2020;Pradeep Prasanna & Charalampopoulos, 2019). Moreover, clinical studies revealed that the addition of probiotic in food product enhance the several mechanisms of action in host health such as altered gut microbiota and restore barrier function (Eor et al, 2020), reduction of postprandial glycemia in healthy (Grom et al, 2020) and prevention of postmenopausal osteoporosis in mouse (Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%